Peningkatan Umur Simpan Produk Santan Kelapa dengan Aplikasi Bahan Tambahan Pangan dan Teknik Pasteurisasi - Nur Wulandari; Indri Lestari; Novi Alfiani (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2017)
Preservation method is needed to maintain the quality and increase the shelf life of coconut milk, one of which is a combination of food additives addition and pasteurization. This study was aimed to determine the effect of food additives addition and pasteurization in extending shelf life of coconut milk. The study was conducted by using coconut milk and it started by determining of coconut blanching method, followed by producing coconut milk (treated by non-preheating and preheating process in 75°C for 15 minutes), addition of food additives (antioxidants, stabilizers, emulsifiers, preservatives), packaging, and pasteurization (75°C for 30 minutes). The quality of coconut milk was observed during storage in room temperature. The results showed that the best blanching method was hot water method at 90°C for 5 minutes. While the best antioxidants, stabilizers, and preservatives for non-preheating coconut milk were butilatedhydroxytoluene (BHT), carboxymethylcellulose (CMC), and methylparaben respectively, whereas for preheating coconut milk were BHT, carrageenan, and potassium sorbate consecutively. In addition, it was also known that the addition of food additives, preheating treatment, and pasteurization had a significant effect on decreasing the number of microbes and being able to maintain changes in pH, free fatty acids, emulsion stability, and organoleptic quality during storage, so that it can extended the shelf life of coconut milk.